Tingkat Pengetahuan terhadap Penanganan Penyakit Rheumatoid Artritis pada Lansia - Juli Andri; Padila Padila; Andry Sartika; Selviyana Ega Nanang Putri; Harsismanto J (Jurnal Kesmas Asclepius, 2020)
This study aims to determine the relationship between the level of knowledge and the management of rheumatoid arthritis in the elderly in BPPLU Fence Dewa Bengkulu City. This study used an analytic observational method with a correlation study design. The results of the univariate analysis showed that 52% of the elderly had a good level of knowledge and 52% of the elderly had good management of rheumatoid arthritis, while the results of the bivariate analysis showed that the value of P = 0.000. In conclusion, there is a relationship between the level of knowledge and the handling of rheumatoid arthritis in the elderly at the Pagar Dewa Elderly Service and Assistance Center, Bengkulu City. Keywords: Elderly, Rheumatoid arthritis, Knowledge Level